Determination of 2,4,6-Trinitrotoluene in Wastes and Sewage Water from Mining Industry by Chromato-Mass Spectrometry - N. V. Zhuravlyov; R. R. Potokina; Z. R. Ismagilov (Eurasian Chemico-Technological Journal, 2013)
A method for determination of 2,4,6-trinitrotoluene in geoenvironmental subjects by gas chromatography with mass-spectrometric detection was proposed. The distribution of 2,4,6-trinitrotoluene in wastes and sewage water samples from mining plants was studied. The presence of this compound in surface water was established. Other nitrogen-containing compounds, in particular, 2-amino-4,6-dinitrotoluene and 2,4,-dinitrotoluene, were also identified in the studied samples. The 2,4,6-trinitrotoluene (TNT) is the most important shattering explosive used for blasting out. This compound is highly toxic and stable to biodegradation. The TNT belongs to the second hazard class (highly hazardous); its maximum permissible concentration (MPC) in drinking water sources was strongly restricted, from 0.5 to 0.01 mg/L. A method for determination of 2,4,6-trinitrotoluene in surface water, sewage water and wastes by gas chromatography with mass-spectrometric detection has been developed. The TNT calibration curve was shown to be linear over the concentration range of 1.6-160 μg/mL, and the correlation factor of the line was equal to 0.997. The distribution of 2,4,6-trinitrotoluene in sewage water and wastes from mining plants has been studied. Mine water in the case of underground mining has high TNT concentrations, which cannot be decreased by the existing traditional methods of sewage water treatment. TNT is detected also in surface water after mine water disposal. Note that the TNT concentrations can exceed many times the maximum permissible concentrations prescribed for water works system. 2-amino-4,6-dinitrotoluene and 2,4,-dinitrotoluene, which can be considered as products of TNT metabolism, were also identified in the studied samples. The developed method and results of the present study make it possible to introduce the quantitative  determination of TNT and its metabolites into the programs for monitoring of surface water, sewage water and wastes in the mining plant sites in different countries as well in Russia, namely in Kuzbass.